Targeted re-sequencing analysis of 25 genes commonly mutated in myeloid disorders in del(5q) myelodysplastic syndromes. - Fernandez-Mercado, M; Burns, A; Pellagatti, A; Giagounidis, A; Germing, U; Agirre, X; Prosper, F; Aul, C; Killick, S; Wainscoat, J; Schuh, A; Boultwood, J (2013)
Interstitial deletion of chromosome 5q is the most common chromosomal abnormality in myelodysplastic syndromes. The catalogue of genes involved in the molecular pathogenesis of myelodysplastic syndromes is rapidly expanding and next-generation sequencing technology allows detection of these mutations at great depth. Here we describe the design, validation and application of a targeted next-generation sequencing approach to simultaneously screen 25 genes mutated in myeloid malignancies. We used this method alongside single nucleotide polymorphism-array technology to characterize the mutational and cytogenetic profile of 43 cases of early or advanced del(5q) myelodysplastic syndromes. A total of 29 mutations were detected in our cohort. Overall, 45% of early and 66.7% of advanced cases had at least one mutation. Genes with the highest mutation frequency among advanced cases were TP53 and ASXL1 (25% of patients each). These showed a lower mutation frequency in cases of 5q- syndrome (4.5% and 13.6%, respectively), suggesting a role in disease progression in del(5q) myelodysplastic syndromes. Fifty-two percent of mutations identified were in genes involved in epigenetic regulation (ASXL1, TET2, DNMT3A and JAK2). Six mutations had allele frequencies <20%, likely below the detection limit of traditional sequencing methods. Genomic array data showed that cases of advanced del(5q) myelodysplastic syndrome had a complex background of cytogenetic aberrations, often encompassing genes involved in myeloid disorders. Our study is the first to investigate the molecular pathogenesis of early and advanced del(5q) myelodysplastic syndromes using next-generation sequencing technology on a large panel of genes frequently mutated in myeloid malignancies, further illuminating the molecular landscape of del(5q) myelodysplastic syndromes.